Spectroscopic signatures of the vanishing natural coronagraph of Eta Carinae. Issue 1 (17th May 2021) - Damineli, A; Navarete, F; Hillier, D J; Moffat, A F J; Corcoran, M F; Gull, T R; Richardson, N D; Weigelt, G; Morris, P W; Stevens, I
ABSTRACT: Eta Carinae is a massive interacting binary system shrouded in a complex circumstellar environment whose evolution is the source of the long-term brightening observed during the last 80 yr. An occulter, acting as a natural coronagraph, impacts observations from our perspective, but not from most other directions. Other sight-lines are visible to us through studies of the Homunculus reflection nebula. The coronagraph appears to be vanishing, decreasing the extinction towards the central star, and causing the star's secular brightening. In contrast, the Homunculus remains at an almost constant brightness. The coronagraph primarily suppresses the stellar continuum, to a lesser extent the wind lines, and not the circumstellar emission lines. This explains why the absolute values of equivalent widths (EWs) of the emission lines in our direct view are larger than those seen in reflected by the Homunculus, why the direct view absolute EWs are decreasing with time, and why lower-excitation spectral wind lines formed at larger radii (e.g Fe ii 4585 Å) decrease in intensity at a faster pace than higher excitation lines that form closer to the star (e.g. H δ). Our main result is that the star, despite its 10-fold brightening over two decades, is relatively stable. A vanishing coronagraph that can explain both the large flux evolution and the much weaker spectral evolution. This is contrary to suggestions that the long-term variability is intrinsic to the primary star that is still recovering from the Great Eruption with a decreasing mass-loss rate and a polar wind that is evolving at a slower pace than at the equator.